(untitled) (Communication & Society, 2010)
The aim of this article is to analyse which role fiction plays in columns, specifically the practice known as self-fiction in the literary research field. It consists of the creation of a fictitious personality with the same name and surnames as the author’s. On the other hand, I will study why columns and short fiction can be swapped. This research will be based on the columns that the writer Empar Moliner publishes in the newspaper Avui. That will allow me to check the experimental nature of this genre and the persuasive value of fiction when used with an argumentative purpose.